The potential of ethnomathematical and mathematical connections in the pre-service mathematics teachers’ meaningful learning when problems-solving about brick-making - Rodríguez-Nieto, Camilo Andrés; Pabón-Navarro, María Luisa; Cantillo-Rudas, Benilda María; Sudirman; Font Moll, Vicenç (IKIP Siliwangi and I-MES, 2025)
This research explores the potential of ethnomathematical and mathematical connections in fostering meaningful learning through problem-solving in brick-making. Despite the importance of such connections in mathematics education, students often struggle with contextualized verbal problems related to daily life. A qualitative ethnographic methodology involved a workshop divided into three stages. Fourteen pre-service mathematics teachers in northern Colombia enrolled in an ethnomathematics course participated. Participant observation was used during the workshop to document how students solved problems and engaged with the material. Data analysis was guided by the Extended Theory of Connections and the Onto-semiotic Approach. The study examined the mathematics emerging from brick production, focusing on problems involving area, volume, and proportional reasoning. Ethnomathematical connections were emphasized, providing a foundation for pre-service teachers to solve problems related to the area and volume of bricks. Various mathematical connections were identified, such as representation, procedural understanding, meaning, and modelling. The research concluded with feedback from researchers, highlighting the educational potential of integrating mathematics with real-world tasks like brick-making. This study provides valuable insights for pre-service teachers in designing contextualized, meaningful math problems.